KONSTRUKSI SOSIAL TERHADAF RIBA DAN ALTERNATIFNYA: (STUDI WACANA PADA MAHASISWA EKONOMI SYARIAH DI STAI SULTHAN SYARIF HASYIM SIAK SRI INDRAPURA RIAU TAHUN 2023-2025) - Wiwik Indra Mariana (STAI Sulthan Syarif Hasyim, 2025)
This study aims to understand how Islamic Economics students at STAI Sultan Syarif Hasyim Siak Sri Indrapura, Riau, during the 2023–2025 period, construct their social understanding of riba and its alternatives. Riba, as a fundamental issue in Islamic economics, is not only viewed as a normative prohibition but also as a social phenomenon constructed through interactions, academic discussions, religious communities, and digital media. The research uses a qualitative method with a discourse analysis approach, grounded in Berger & Luckmann’s theory of social construction. Data were collected through in-depth interviews, participatory observation, and documentation of student activities. Data analysis was carried out through data reduction, thematic categorization, and triangulation to ensure validity. The findings show that students construct riba through three main discourse forms: Normative–religious, emphasizing riba as a major sin and a clear prohibition in Islamic law, Critical–social, viewing riba as an exploitative and unjust system and Practical alternatives, offering solutions through Islamic contracts (murabahah, mudharabah, musyarakah, ijarah), Islamic fintech, and productive waqf. The campus environment, social communities, and digital media play significant roles in strengthening these discourses and shaping students’ collective identity as intellectual and social agents. The dynamics of student discourse during 2023–2025 indicate a strengthening of sharia literacy, the digitalization of discourse, and the integration of social–spiritual values, although challenges remain, including conceptual ambiguity, dominance of the conventional financial system, and limited sharia-compliant infrastructure. The study concludes that students’ social construction of riba is not a static phenomenon, but a dynamic process that continues to evolve according to local and global contexts. These findings are expected to enrich academic literature, strengthen the development of Islamic economics curricula, and provide practical recommendations for campuses and student communities in building a just, riba-free financial system.